AUDIT TEKNOLOGI INFORMASI PADA DEALER MOBIL XYZ DI BANDAR LAMPUNG DENGAN MENGGUNAKAN PENDEKATAN COBIT 4.1 - Lilis Oktaviani Sirait; Tristiyanto Tristiyanto (Universitas Lampung, 2017)
Information technology is growing rapidly and greatly influences to improving the effieciency and effectiveness of business activities in developing the company. In this case, an information technology audit is needed to ensure the existing information technology, that has been already satisfy the common control standards and has the ability to compete in the business world. The purpose of this research is to evaluate the assessment and to make recommendations based on the analysis maturity level of IT in Car Dealer XYZ in Bandar Lampung according to the framework COBIT 4.1. Standard of COBIT 4.1 has parameters that can aid the assessment of an enterprise using a maturity model. This research finds that the result of maturity level of Car Dealer XYZ in Bandar Lampung is 4.02. This shows that Information Technology has been updated well where the procedures and policies have been done effectively, monitored and there are corrective actions are taken.